Bionomics of black flies (Diptera: Simuliidae) in Costa Rica. III. Larval population dynamics in five selected streams - Travis, B. V. (1979)
Studies on black fly larval populations in five streams in the Central Valley of Costa Rica during July 1968 to July 1969 indicated that a single observation on a stream would not necessarily evaluate its relative importance as a black fly producer and that more than one sampling is needed to obtain reliable and representative data.Among the subgenera studied (Hemicnetha, Psilopelmia and Simulium) information on larval size, maturity and population levels established that hatching of larvae continued during both dry and rainy seasons. Although the population levels dropped during the dry sea son in three of the five study streams, there was no consistent seasonal influence on larval populations and the differences observed were greater between streams than between seasons.